Kemunduran dan Keruntuhan Ekonomi Muslim Pribumi di Indonesia - Herdi Sahrasad; Ma'mun Al-Barbasy (Budapest International Research and Critics University, 2018)
The article describes abour business circles and the middle class of indigenous Muslims who want the duo of President Jokowi-Jusuf Kalla (Vice President), who replaces SBY-Boedino today, can firmly and quickly put an end to social crime practices, especially how to eradicate corruption, law enforcement, community empowerment, for the sake of justice, humanity, freedom, human rights, and democracy. The Muslim commu- nities want that in this reform era, Jokowi-JK program is accompanied by a